Influence of Driving Fluency on Economic and Ecological Aspects of Transport - Hyks, Oldrich; Neubergova, Kristyna; Pribyl, Pavel (Communications - Scientific letters of the University of Zilina, 2018)
The paper is focused on the influence of driving behaviour on fuel consumption and the subsequent environmental impacts. The main issue is to estimate the economic and environmental costs connected with the forced deceleration or stopping and the subsequent acceleration of a motor vehicle in urban traffic. Authors introduce a physical model of a vehicle with variable parameters that allows the calculation of economic and ecological losses in congestions on the basis of data generated by an arbitrary floating car. The losses include the lost kinetic energy of a vehicle during the forced braking, accelerated degradation of vehicle components, the loss of time of drivers and passengers and the increased ecological footprint. Energetic costs are estimated from the vehicle engine efficiency with which the fuel energy is transformed during an acceleration to kinetic energy of a vehicle lost during braking. Further, these costs are estimated from fuel calorific value and fuel price. Costs resulting from the degradation of vehicle components are estimated from their average stated lifetime.